2017
DOI: 10.1002/asia.201701569
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monofunctionalized Silsesquioxanes (RSiMe2O)(iBu)7Si8O12via Alkene Hydrosilylation

Abstract: The research presented in this work comprehensively describes hydrosilylation of a wide spectrum of alkenes which contain one or more reactive groups with (HSiMe O)(iBu) Si O , in the presence of different types of catalysts. Special attention is paid to the influence of alkene, catalyst, and reaction conditions on process effectiveness and selectivity by the precise monitoring of the experiments with in situ FTIR and NMR spectroscopies. More than twenty silsesquioxanes bearing reactive groups (OH, Br, NR , CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…In obtained styryl derivatives of DDSQ-based system (3 i-k) we suspect statistical distribution of β-(n) and α-(m) substituted fragments in its one molecule rather than formation of two separate molecules of isomeric compounds with all four βand all four αsubstituted moieties (but it should not be omitted). [33,46] Herein, for all applied alkenes except for styrenes, a selective formation of β-hydrosilylation product was noted. Recent studies on the HS of olefins with (HSiMe 2 O)(iBu) 7 Si 8 O 12 have shown high selectivity for Karstedt's catalyst allowing formation of β-hydrosilylation product with high predominance.…”
Section: ] and Based On Rh ([Rhcl(cod)] 2 [Rhcl(pph) 3 ]) And Ir ([Imentioning
confidence: 87%
See 4 more Smart Citations
“…In obtained styryl derivatives of DDSQ-based system (3 i-k) we suspect statistical distribution of β-(n) and α-(m) substituted fragments in its one molecule rather than formation of two separate molecules of isomeric compounds with all four βand all four αsubstituted moieties (but it should not be omitted). [33,46] Herein, for all applied alkenes except for styrenes, a selective formation of β-hydrosilylation product was noted. Recent studies on the HS of olefins with (HSiMe 2 O)(iBu) 7 Si 8 O 12 have shown high selectivity for Karstedt's catalyst allowing formation of β-hydrosilylation product with high predominance.…”
Section: ] and Based On Rh ([Rhcl(cod)] 2 [Rhcl(pph) 3 ]) And Ir ([Imentioning
confidence: 87%
“…However, this À OMe 2 SiÀ H moiety is attached to the T order of Si in 1-DDSQ and Q in (HSiMe 2 O)(iBu) 7 Si 8 O 12 [33] which may affect its reactivity in both cases. There is a resemblance of functional À OMe 2 SiÀ H group in 1-DDSQ and (HSiMe 2 O)(iBu) 7 Si 8 O 12 , i. e. M order of silicon atom.…”
Section: ] and Based On Rh ([Rhcl(cod)] 2 [Rhcl(pph) 3 ]) And Ir ([Imentioning
confidence: 99%
See 3 more Smart Citations